Implementasi Algoritma Kriptografi RSA dalam Proses Enkripsi dan Dekripsi untuk Mengamankan Pesan Singkat pada Aplikasi Chatting Berbasis Web - Surbakti, Nurul; Kartika, Dinda; Lestari, Alya Dwi; Puspita, Maysi; Pandiangan , Petra Putri Sarinah; Singarimbun, Riamonda; Suryani, Windi (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of information technology, especially in online communication, raises concerns about the security and privacy of transmitted messages. Cryptography serves as a primary alternative to protect information from unauthorized access. This study aims to implement the RSA (Rivest Shamir Adleman) cryptographic algorithm to secure short messages in a web-based chat application. The research method used was a mixed method, combining literature study and application development trials. The designed application uses the Flask framework for the backend, while HTML, CSS, and JavaScript are used for the user interface. The implementation results show that the RSA algorithm successfully converted plaintext messages (e.g.,